Edgework : Critical Essays on Knowledge and Politics - Brown, Wendy, 1955- (Book collections on Project MUSE., 2005)
Edgework brings together seven of Wendy Brown's most provocative recent essays in political and cultural theory. They range from explorations of politics post-9/11 to critical reflections on the academic norms governing feminist studies and political theory. Edgework is also concerned with the intellectual and political value of critique itself.